Relationship of servant leadership with employee in-role and extra-role performance in GLC’s of Malaysia - Rashid, Mehwish; Tasmin, Rosmaini; Qureshi, Muhammad Imran; Shafiq, Muhammad (City University Peshawar Pakistan, 2017)
This research aims to study the relationship of servant leadership with employee performance of in-role and extra role performance. Servant leadership, and its relationship with employee OCB and task performance are discussed to start with. Though some literature is available on links of servant leadership with employee task performance or Organizational Citizenship Behaviors, but how these two behaviors interact is not explained much. This paper explains that servant leadership has positive relationship with OCB. Though, other leadership approaches are different from servant leadership as its focus is on personal integrity and lasting relationships with employees.